2018
DOI: 10.1002/bdr2.1376
|View full text |Cite
|
Sign up to set email alerts
|

Mortality factors in infants with congenital diaphragmatic hernia: A systematic review

Abstract: Although the factors of interest showed no significant association with survival, more evidence is required to confirm these findings. Understanding whether sociodemographic factors are associated with survival may help inform the development of public health interventions to improve survival rates for children with CDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
2
0
6
Order By: Relevance
“…A hérnia diafragmática congênita (HDC) é malformação do diafragma que ocorre em 3,5 a cada 10.000 nascidos vivos nos Estados Unidos e 2,3 a cada 10.000 na Europa. 1 No Brasil, segundo dados do DataSUS, em 10 anos (2009-2019) registraram-se 2.502 nascidos vivos com ela. O dado mais recente corresponde ao ano de 2020, em que 276 casos foram detectados.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A hérnia diafragmática congênita (HDC) é malformação do diafragma que ocorre em 3,5 a cada 10.000 nascidos vivos nos Estados Unidos e 2,3 a cada 10.000 na Europa. 1 No Brasil, segundo dados do DataSUS, em 10 anos (2009-2019) registraram-se 2.502 nascidos vivos com ela. O dado mais recente corresponde ao ano de 2020, em que 276 casos foram detectados.…”
Section: Introductionunclassified
“…6 Dentre as herniações mais comuns, está a hérnia de Bochdalek (póstero-lateral) correspondendo a 85-90% dos casos, sendo 80-85% à esquerda, 10-15% à direita, e em menos de 2%, com maior mortalidade, bilateralmente. 1,7 HDC é a condição que resulta na formação incompleta do diafragma, permitindo que os órgãos abdominais invadam a cavidade torácica, propiciando diversas anomalias fisiológicas ao recém-nascido, sobretudo malformações respiratórias por impedimento do desenvolvimento correto dos pulmões. Devido a essa condição, cerca de 87% dos neonatos que sobrevivem à hérnia diafragmática congênita podem evoluir com algumas complicações em curto e médio prazos; dentre elas, pode-se citar doença do refluxo gastroesofágico, dificuldade de alimentação e do crescimento, deformidades esqueléticas e atraso no neurodesenvolvimento.…”
Section: Introductionunclassified
“…Identifying high‐risk patients in the postnatal period is crucial regarding patient management and treatment strategies 3 . It has been revealed that in low birth weight or preterm infants, CDH progresses poorly, and the survival rate is low 2,4–6 . The degree of pulmonary hypoplasia, the adequacy of ventilation oxygenation and pulmonary hypertension determines the course of CDH 1,2,7 .…”
Section: Introductionmentioning
confidence: 99%
“…3 It has been revealed that in low birth weight or preterm infants, CDH progresses poorly, and the survival rate is low. 2,[4][5][6] The degree of pulmonary hypoplasia, the adequacy of ventilation oxygenation and pulmonary hypertension determines the course of CDH. 1,2,7 In 2014, a clinical prediction rule consisting of birth weight, 5-min Apgar score, pulmonary hypertension, accompanying chromosomal anomaly, or congenital cardiac anomalies was developed by the Congenital Diaphragmatic Hernia Study Group (CDHSG) to determine the severity of CDH.…”
Section: Introductionmentioning
confidence: 99%
“…Modalidades avançadas de VPM, como a ventilação de alta frequência oscilatória, a terapia de suporte à vida pela Oxigenação por Membrana Extracorpórea (ECMO) e o reparo cirúrgico do defeito, associados ao melhor conhecimento e manejo dos RN, são fatores que melhoram a sobrevida da HDC 27 .…”
Section: Hérnia Diafragmática Congênitaunclassified